2016
DOI: 10.1002/cbic.201600453
|View full text |Cite
|
Sign up to set email alerts
|

Guide Strand 3′‐End Modifications Regulate siRNA Specificity

Abstract: Short interfering RNA (siRNA)-triggered gene knockdown via the RNA interference (RNAi) pathway is widely used to study gene function and siRNA-based therapeutics are in development. However, since the guide strand of an siRNA can function like a natural microRNA (miRNA), siRNAs often repress hundreds of off-target transcripts with complementary only to the seed region (nucleotides 2–8) of the guide strand. Here we describe novel guide strand 3′ end modifications derived from 1-ethynylribose and copper-catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Additionally, the presence of the maleimide on the 3’ terminal of the siRNA sequence may impact the activity of the siRNA. Previous studies indicate that siRNA retain RNAi activity after 3’ modification with several different chemical moieties [68] [69] [70], but at this time, it is not clear what effect, if any, the 3’ maleimide modification has on the siRNA’s ability to interact with the 3’ UTR region of mRNA. Further studies are required to address this concern.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of the maleimide on the 3’ terminal of the siRNA sequence may impact the activity of the siRNA. Previous studies indicate that siRNA retain RNAi activity after 3’ modification with several different chemical moieties [68] [69] [70], but at this time, it is not clear what effect, if any, the 3’ maleimide modification has on the siRNA’s ability to interact with the 3’ UTR region of mRNA. Further studies are required to address this concern.…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 7 The development of chemical modifications has been the focus of recent research, in which attention has been directed towards RNA modifications that enable the avoidance of sense strand-mediated and miRNA-like off-targeting effects. 8 12 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the 3 0 -end of the sense strand is able to accommodate bulky groups. 25 The wild-type siRNA (wt), which lacks a cholesterol modication, did not display any gene-silencing activity in our carrierfree study. This was expected as unmodied siRNAs are known to have difficulties in crossing the cellular membrane unassisted.…”
mentioning
confidence: 73%